Inkjet‐ and FlexTrail‐Printing with Low Silver Consumption for Silicon Heterojunction Solar Cells. Issue 9 (13th September 2019) - Schube, Jörg; Fellmeth, Tobias; Jahn, Mike; Keding, Roman; Glunz, Stefan W.
Abstract : A novel printing technology, called FlexTrail printing, is introduced in article no.1900186 . Utilizing a commercial Ag nanoparticle ink, the mean finger width is reduced down to 16 μm on the front side of silicon heterojunction solar cells. They exhibit alkaline textured surfaces covered with indium tin oxide layers. The inherent characteristic of FlexTrail printing enables interruption‐free ink application as well as high tolerance towards ink formulation and process temperature. Furthermore, FlexTrail printing offers a high throughput potential and low ink laydown. Finally, the extremely narrow fingers printed on heterojunction cells' front sides enable very high conversion efficiencies.